Increases in Perspective Embedding Increase Reading Time Even with Typical Text Presentation: Implications for the Reading of Literature - Whalen, D. H.; Zunshine, Lisa; Holquist, Michael (Frontiers in Psychology, 2015)
Reading fiction is a major component of intellectual life, yet it has proven difficult to study experimentally. One aspect of literature that has recently come to light is perspective embedding ("she thought I left" embedding her perspective on "I left"), which seems to be a defining feature of fiction. Previous work (Whalen et al., 2012) has shown that increasing levels of embedment affects the time that it takes readers to read and understand short vignettes in a moving window paradigm. With increasing levels of embedment from 1-5, reading times in a moving window paradigm rose almost linearly. However, level 0 was as slow as 3-4. Accuracy on probe questions was relatively constant until dropping at the fifth level. Here, we assessed this effect in a more ecologically valid (“typical”) reading paradigm, in which the entire vignette was visible at once, either for as long as desired (Experiment 1) or a fixed time (Experiment 2). In Experiment 1, reading times followed a pattern similar to that of the previous experiment, with some differences in absolute speed. Accuracy matched previous results: fairly consistent accuracy until a decline at level 5, indicating that both presentation methods allowed understanding. In Experiment 2, accuracy was somewhat reduced, perhaps because participants were less successful at allocating their attention than they were during the earlier experiment; however, the pattern was the same. It seems that literature does not, on average, use easiest reading level but rather uses a middle ground that challenges the reader, but not too much.